Political Aspects in Educational Leadership: A Case Study in ASEAN Economic Community Era - Ferry Doringin; Kristianus Oktriono (Bina Nusantara University, 2017)
The objective of this research was to see the political aspects in the success of educational leader using qualitative case study method. Leaders must realize their roles as a CEO, as an academician, and as a political leader. The research problem was why did the educational leaders had difficulty to take their role as political leaders and how to inspire them doing the role? The research applied a qualitative method by using “how” and “why” questions for analysis. There were some complicated issues in educational activities that were difficult to be solved but became easier if educational leaders have skills in persuading, negotiating, and using political process. The significant of the study was to inspire the educational leaders that they did not only take their role as the CEO, or the academician, but also the role as political leaders to be more successful in leading. Vocational and Training institutions in Indonesia face some challenges to be successful in ASEAN Economic Community (AEC) era. The leaders of the institutions will be more successful if they understand the political roles, political process, and political techniques.